Development knowledge expert repository system for IT professionals at CICT, UTM - Ishak, Zam Zarina (2006)
ICT is rapidly changing. Rapid changes in ICT causes the skills and knowledge required IT Professionals to change in order to update and upgrade their IT skills and knowledge. Furthermore, the rapid innovations in ICT are resulting in fast changing requirement and the need of knowledge sharing among the IT Professionals. One of the objectives of this study is to identify the required skills and knowledge required by the IT Professionals at CICT. Then, based on the information, IT Expertise Framework is formulated. The project solution goes through project initiation and planning, designs system, develop prototype, build final system, perform user acceptance testing, finalize system and report writing. The information was collected by interviewing CICT top management and end user, study past literature review such as journals, books and website. A Unified Modeling Language is use in the conceptual designs that are use case, class diagram and sequence diagram. The end results for this project are IT Expertise Framework and Knowledge Expert Repository System (KERYS). IT Expertise Framework is a dynamic framework that categorized IT skills into 3 main categories, which are technical skills, soft skills and business skills. Then IT Expertise Framework is mapped into KERYS that able to store and gather expertise information. Furthermore, this system will provide an effective ways and venue for the IT Professionals to share expertise and knowledge that encourage collaboration and commitment towards lifelong learning.